Case report: Transformative potential of trastuzumab deruxtecan in the first line treatment for advanced HER2-mutated lung adenocarcinoma: a case report and clinical insights - Huang, Guanbin; Xia, Tongtong; Yang, Dongxiao; Lin, Muwen; Luo, Yiping; Li, Yuchan; Chen, Hualin (Frontiers in Pharmacology, 2025)
The treatment of non-small cell lung cancer (NSCLC), particularly lung adenocarcinoma (LUAD), represents a significant oncological challenge due to its aggressive behavior, high metastatic potential and poor prognosis. HER2 mutation is a rare but critical oncogenic driver associated with resistance to traditional therapies among NSCLC subtypes, including chemotherapy and tyrosine kinase inhibitors (TKIs). Trastuzumab deruxtecan (T-DXd), a next-generation antibody-drug conjugate, combines HER2-targeted therapy with a potent cytotoxic payload, enabling specific tumor cell eradication and addressing intratumoral heterogeneity through its bystander effect. This case report details the treatment of a 69-year-old male with advanced HER2 exon 20-mutant LUAD and widespread metastases. Following the family’s refusal of chemotherapy, T-DXd was initiated, leading to prolonged disease stabilization over 14 treatment cycles, demonstrating a progression-free survival of at least 13 months. Imaging assessments revealed a consistent reduction in the primary lung lesion size, with stable disease (SD) observed according to RECIST criteria. Despite a mixed response in brain metastases, T-DXd demonstrated a favorable safety profile without significant adverse events. While pivotal trials such as DESTINY-Lung02 and DESTINY-Lung05 have demonstrated robust efficacy and survival benefits of T-DXd as subsequent lines of therapy, our patient’s tolerance and sustained SD support the therapeutic potential of T-DXd as a first line treatment in certain real-world scenarios. In addition, this case reinforces the importance of molecular profiling in guiding personalized treatment strategies and highlights the need for further research, particularly in overcoming challenges related to central nervous system metastases. Overall, T-DXd represents a promising advancement in HER2-mutant NSCLC management, offering hope for improved outcomes in this underserved patient population.